Instructional leadership in Greek and English outstanding schools. Issue 6 (8th August 2016) - Kaparou, Maria; Bush, Tony
Abstract : Purpose: This research paper examines instructional leadership in outstanding secondary schools within a centralised (Greece) and a partially decentralised (England) education context. Design/methodology/approach: Since the purpose of the study is exploratory, the researchers adopt a qualitative approach, employing a series of four qualitative case studies with the purpose of examining the impact of instructional leadership on student learning, teachers' professional growth and school improvement, using the interpretivist paradigm. Semi-structured interviews with various data sets (stakeholders) within and outside the school, observation of leadership practices and meetings, and scrutiny of relevant macro and micro policy documents are employed to enhance methodological and respondent triangulation. Findings: Recognising that instructional leadership is not confined to the principals' leadership domain, a sense of shared and distributed leadership prevails in schools, while its implementation is inevitably linked to system constraints. The findings from the Greek schools link to the official expectations that principals operate as administrative rather than instructional leaders, while an unofficial instructional 'teacher leadership' culture suggests potential for reconsidering leadership in Greek state schools. In contrast, the decentralization of school activities creates the platform for the emergence of shared and distributed leadership within the English context, where school actors enact direct and indirect instructional leadership roles. Originality/value: This cross-country comparative study demonstrates theoretical significance in its focus on the collaborative and reciprocal nature of instructional leadership, while its empirical contribution lies in generating new knowledge on how instructional leadership is contextually bounded.